Increasing Knowledge And Attitudes Towards Organic Waste Processing Through Demonstration Of BSF (Black Soldier Fly) Maggot Cultivation Practices At Darul Fikri Islamic Boarding School, Sungai Belidak - Diki Fahrozi Almuharami; Selviana, Selviana; Elly Trisnawati (Jurnal EduHealth, 2024)
Darul Fikri Islamic Boarding School, as an Islamic educational institution andreligious tourism destination, produces a large amount of organic waste, impropermanagement of organic waste can have a negative impact on the environment. BSF maggot cultivation offers a potential solution to overcome the problem oforganic waste, this study aims to measure the effectiveness of BSF maggotcultivation practices in improving students' knowledge and attitudes towardsorganic waste management at Darul Fikri Islamic Boarding School, this study used a quasi-experimental one-group pretest-posttest design, A total of 30 students became respondents and were given questionnaires before and afterparticipating in the BSF maggot cultivation practice. Data were analyzed using a paired t-test to test the difference in scores between the pretest and posttest. The results showed a very significant increase (p value <0.05) in the knowledge andattitudes of students after participating in the BSF maggot cultivation practice, this indicates that the demonstration method is an effective approach in increasingstudents' awareness and skills in managing organic waste. The practice of BSF maggot cultivation has proven effective in improving students' knowledge andattitudes towards organic waste management. This approach can be a model thatcan be applied in other educational institutions to encourage environmentallyfriendly behavior.